(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
The Malay Community from the past to the present is often associated with debt. This paper describes the reason and the behavior of the Malays involved in monetary borrowing since before Malaysia achieved independence. This paper uses a qualitative method and the description is based on past studies, historical records and Bank Negara Malaysia’s Annual Report 2015. We found that the Malays fall into debt not just to meet their necessities in the case of poor people, but in the case of the rich, for luxury and to improve their social status. The practice of monetary borrowing has had a detrimental impact on the present generation, as thousands of hectares of Malay land were pledged to the Chettiars, as a result of failure to repay debt due to high interest rates and oppressive creditors. Going into debt for reasons other than necessity is still the practice today. Keywords: Malay community, debt, Chettiar community, Malay land